DVB-T2 reception in Jurong HDB estate - Yu, Jianshu (2014)
DVB-T2 is a standard for digital terrestrial television. It was published by the ETSI in 2009. Comparing to the standard of DVB-T, it provides more options in parameters setting, such as more number of carriers in signal, additional modulation formats and extra guard intervals. Singapore's MediaCorp has turned all free-to-air terrestrial TV channels fully digitalized by the end of 2013 using the DVB-T2 standard. Though both DVB-T and analog will be simulcast together with DVB-T2 for a long time, DVB-T2 standard based digital TV Terrestrial Broadcasting will be the mainstream of TV broadcasting in Singapore in the near future. Hence, there is a need to measure the current digital TV signal's quality in Singapore, especially in residential district such as HDB estate.